2021
DOI: 10.3390/d13060228
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Natural Products NOZEMAT HERB and NOZEMAT HERB PLUS Can Decrease Honey Bee Colonies Losses during the Winter

Abstract: Honey bees (Apis mellifera L.) are crucial pollinators for many crops and natural ecosystems. However, honey bee colonies have been experiencing heavy overwinter mortality in almost all parts of the world. In the present study we have investigatеd, for the first time, the effects from the application of the herbal supplements NOZEMAT HERB® (NH) and NOZEMAT HERB PLUS® (NHP) on overwintering honey bee colony survival and on total protein and lysozyme content. To achieve this, in early autumn 2019, 45 colonies we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 100 publications
0
6
0
Order By: Relevance
“…Herbal supplements (with or without C vitamin), have shown to reduce the N. ceranae infection levels in affected honey bee colonies enhancing their strength [68] and reducing the winter mortality [69]. Feeds containing Brassica nigra and Eruca sativa, with different amounts of glucosinolates (GSLs), reduced the N. ceranae infection [70].…”
Section: Phytotherapeuticsmentioning
confidence: 99%
“…Herbal supplements (with or without C vitamin), have shown to reduce the N. ceranae infection levels in affected honey bee colonies enhancing their strength [68] and reducing the winter mortality [69]. Feeds containing Brassica nigra and Eruca sativa, with different amounts of glucosinolates (GSLs), reduced the N. ceranae infection [70].…”
Section: Phytotherapeuticsmentioning
confidence: 99%
“…Another study investigated the effect of two Laurus nobilis L. extracts on colony strength [48], and the obtained results demonstrated that the hydroalcoholic extract from the aromatic herb clearly had a positive impact on honey bee colonies strength, presumably due to the antioxidant effect related to the phenolic compounds contained in the hydroalcoholic extract. Our previous research [49] has also shown the benefi cial effect on honey bee colony strength from the application of two plant extracts (produced by Extract Pharma, Sofi a, Bulgaria) -NOZEMAT HERB® (1.65 ± 0.05 kg) and NOZEMAT HERB PLUS® (1.63 ± 0.12 kg). It should be noted that the treatment with IMMUNOSTART HERB® resulted in an additional increase of about 0.5 kg in the mass of frames (kg) covered with bees, i.e.…”
Section: Discussionmentioning
confidence: 91%
“…Thus, there is an urgent need for controlling the feeding process of bees as an effective method to enrich honey with desirable bioactive plant components, which can be achieved using natural herbs. This method is considered a creative and innovative way of producing bee products rich in bioactive compounds as reported by recent studies (e.g., [ 41 , 42 , 43 , 44 ]). These bioactive compounds mainly depend on the plant species, such as the coumarin in the case of using the flowers of the Melilotus officinalis herb [ 42 ], or patented herbal extract [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…This method is considered a creative and innovative way of producing bee products rich in bioactive compounds as reported by recent studies (e.g., [ 41 , 42 , 43 , 44 ]). These bioactive compounds mainly depend on the plant species, such as the coumarin in the case of using the flowers of the Melilotus officinalis herb [ 42 ], or patented herbal extract [ 44 ]. This current study is a new and patented technology, crucial as a new solution for supporting beekeepers and their feeding of bees with a preservative material as compared to the known beekeeping technologies.…”
Section: Discussionmentioning
confidence: 99%